Subjective Cognitive Decline May Be Associated With Post-operative Delirium in Patients Undergoing Total Hip Replacement: The PNDABLE Study - Lin, Xu; Liu, Fanghao; Wang, Bin; Dong, Rui; Sun, Lixin; Wang, Mingshan; Bi, Yanlin (Frontiers in Aging Neuroscience, 2021)
ABSTRACT Objective: Subjective cognitive decline (SCD) is associated with an increased risk of clinical cognitive disorders. Postoperative delirium (POD) is a common complication after total hip replacement. We aimed to investigate the relationship between SCD and POD in patients undergoing total hip replacement. Methods: Our study recruited 214 cognitively intact individuals from the Perioperative Neurocognitive Disorder And Biomarker Lifestyle (PNDABLE) study in the final analysis. SCD was diagnosed with Subjective Cognitive Decline Scale (SCDS), Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA). The incidence of POD was evaluated by using Confusion Assessment Method (CAM), and POD severity was measured by using the Memorial Delirium Assessment Scale (MDAS). Preoperative cerebrospinal fluid (CSF) Aβ40、Aβ42、T-tau and P-tau levels were measured by enzyme-linked immune-sorbent assay (ELISA). Results: Overall, the incidence of POD was 26.64% (57/214), 32.43% (36/111) in SCD group and 20.39% (21/103) in NC group. With the increase of age, the incidence of POD increased in different age groups ( P < 0.05). Logistic regression analysis showed that after adjusting for SCD, Aβ42, Aβ40, P-tau and T-tau . SCD (OR 2.32, CI 1.18 to 4.55, P=0.01) and the increased level of P-tau (OR 1.04, CI 1.01 to 1.06, P<0.001) in CSF were risk factors for POD, while the level of aβ42 (OR 0.99, CI 0.99 to 1.00, P<0.001) was a protective factor for POD. Conclusion: SCD is one of the preoperative risk factors for POD.